2009
DOI: 10.1002/aur.109
|View full text |Cite
|
Sign up to set email alerts
|

A pharmacogenetic study of escitalopram in autism spectrum disorders

Abstract: Scientific AbstractObjective-To determine the effect of serotonin transporter polymorphism promoter region (5-HTTPLR) genotypic variation (low, intermediate, and high expression groups) on response to escitalopram treatment of children and adolescents with Autism Spectrum Disorders (ASDs).Method-The study used a forced titration, open label design, with genotype blind until study completion. Participants were children and adolescents aged 4 to 17 years of age with a confirmed ASD (Autistic Disorder, Asperger's… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
60
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(66 citation statements)
references
References 28 publications
4
60
2
Order By: Relevance
“…In contrast, participants in the SS group showed significant improvement in delayed speech or peculiar or inappropriate speech. In an open label study (blind to genotype) with escitalopram (n = 58), the LL and SL groups showed a greater reduction in the Aberrant Behavior Checklist-Irritability factor (Aman et al 1985) scores than did the SS group (Owley et al 2010). The direction of these findings is generally consistent with those found in pharmacogenetic studies of major depressive disorder (Serretti et al 2007).…”
supporting
confidence: 61%
See 3 more Smart Citations
“…In contrast, participants in the SS group showed significant improvement in delayed speech or peculiar or inappropriate speech. In an open label study (blind to genotype) with escitalopram (n = 58), the LL and SL groups showed a greater reduction in the Aberrant Behavior Checklist-Irritability factor (Aman et al 1985) scores than did the SS group (Owley et al 2010). The direction of these findings is generally consistent with those found in pharmacogenetic studies of major depressive disorder (Serretti et al 2007).…”
supporting
confidence: 61%
“…Our study is the first study to look at the response to SSRI in ASD as a function of both 5HTTLPR and HTR2A genotypes. Owley et al (2010) observed smaller decreases (less response) in irritability on the ABC-CV in the 5HTTLPR SS group than in the SL and LL groups. Sugie et al (2005) not only identified that subjects with SS genotypes had less response as measured by the CGI Severity scale, but also that the S allele was associated with significant improvement in language on the Behavioral Assessment Scale (BAS).…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…For example, studies using pharmacogenomics and clinical trials would allow clinicians todetermine which medication in a certain class would be best for treating specific symptoms. 8,9 …”
Section: A Platform For Researchmentioning
confidence: 99%